A convenient strategy to synthesize highly tunable gelatin methacryloyl with very low gelation temperature. (5th July 2021) - Di Muzio, Laura; Cienzo, Federica; Paolicelli, Patrizia; Petralito, Stefania; Garzoli, Stefania; Brandelli, Chiara; Trilli, Jordan; Antonietta Casadei, Maria
Graphical abstract: Highlights: Novel procedure to synthesize gelatin methacryloyl under single-phase conditions. Synthesis of gelatin derivatives with tunable and highly reproducible methacrylation degree. The synthetic procedure affects the rheological behaviour of gelatin methacryloyl. Abstract: Gelatin methacryloyl (GelMA) is a polymeric derivative of gelatin (Gel) widely used in tissue engineering, as well as in wound dressing and drug delivery field. This work offers an alternative and convenient method for the synthesis and characterization of GelMA. In particular, the methacrylation was carried out under homogeneous single-phase reaction conditions, which allows of obtaining a good reproducibility of the derivatization degree of the polymer in a simple and fast way. The experimental conditions were adequately optimized to have the methacrylation of only ε-amino groups of lysine and hydroxylysine, as confirmed by FT-IR and 1 H NMR analysis. The degree of derivatization of GelMA was determined using an internal standard applied to 1 H NMR analysis. Based on these measurements, it was found that the optimized reaction proceeds to complete functionalization of ε-amino groups of lysine and hydroxylysine. The effect of the reaction conditions on the rheological properties of GelMA was investigated through temperature sweep experiments and compared with those of the polymer obtained under traditional heterogeneous reaction conditions. A significant difference was found in the gelation temperature of GelMA synthesized following the two different procedures. In particular, the proposed single-phase synthetic protocol gave a polymer which behaves like a solution when used at 10% w/v concentration and even at temperatures as low as 5 °C, whereas the polymer obtained with the classic biphasic procedure behaves like a gel within the same range of temperatures and when used at the same concentration. These results are particularly interesting as they could open GelMA to new applications particularly in the biomedical field.